2021
DOI: 10.3390/v13061098
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Molecular Epidemiological Analysis of SARS-CoV-2 Infection in Cyprus from April 2020 to January 2021: Evidence of a Highly Polyphyletic and Evolving Epidemic

Abstract: The spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) resulted in an extraordinary global public health crisis. In early 2020, Cyprus, among other European countries, was affected by the SARS-CoV-2 epidemic and adopted lockdown measures in March 2020 to limit the initial outbreak on the island. In this study, we performed a comprehensive retrospective molecular epidemiological analysis (genetic, phylogenetic, phylodynamic and phylogeographic analyses) of SARS-CoV-2 isolates in Cyprus from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 78 publications
4
27
0
Order By: Relevance
“…D1118H: This mutation was detected first in the B.1.1.7 UK variant. The D1118H substitution is also present in the S2 subunit of the S protein ( Chrysostomou et al., 2021 ). It has been suggested that this mutation can alter the stability and dynamics of trimer assembly ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…D1118H: This mutation was detected first in the B.1.1.7 UK variant. The D1118H substitution is also present in the S2 subunit of the S protein ( Chrysostomou et al., 2021 ). It has been suggested that this mutation can alter the stability and dynamics of trimer assembly ( Zhao et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyprus was no exception with regard to this pattern of lineage replacement, with certain lineages causing surges of new infections, reaching a distinct peak and then a decline; this peaks-and-valleys pattern is referred to as ‘waves’ [ 27 , 28 ]. Specifically, in our previous study covering the period of April 2020 to January 2021, we determined that despite polyphyletic infection in Cyprus with 34 different lineages, there were three consecutive waves characterized by specific lineages [ 29 ]: B.1.1, specifically B.1.1.29, comprising the first wave with sequences from April 2020 to June 2020; B.1.258 & sublineages comprising the second wave, with sequences from September 2020 to January 2021; and Alpha (B.1.1.7 & Q. sublineages), comprising the beginning of the third wave, with sequences from December 2020 until the end of the sampling period in January 2021 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination campaigns against SARS-CoV-2 have been gathering momentum, but most countries remain months away from reaching group immunity [ 1 - 4 ], provided that such immunity can be attained [ 5 , 6 ]. The almost incessant emergence of new variants is concerning [ 7 ]—all the more so as some variants have been shown to evade the immune response acquired by vaccination or by prior infection [ 8 , 9 ]. Viral dissemination may even be facilitated, if normal social interactions are restored and social distancing measures are eliminated, as countries face ever increasing social and economic pressures [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%